2017
DOI: 10.1177/1942602x17743985
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Best Evidence to Support Care of Students With Chronic Conditions: CLUE #2: Acquire

Abstract: Every day, school nurses make practice decisions that impact the care provided to school children. Our professional standards require that we stay up to date with best practice options, yet there is neither time nor money to attend a continuing education offering for every practice concern we encounter. Learning how to acquire the evidence that leads to best practice can ensure our practice is current and that our students have the best chance to have positive health and academic outcomes. This article explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, it may be prudent to look to see if a more recent review has been completed that focuses on Benadryl versus epinephrine to ensure the evidence has not changed. Table 1 outlines the questions and results for the second article by Cheung et al (2015) identified in the previous article (Yonkaitis & Maughan, 2018). You will note the results are not perfect.…”
Section: • • Systematic Reviews/meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may be prudent to look to see if a more recent review has been completed that focuses on Benadryl versus epinephrine to ensure the evidence has not changed. Table 1 outlines the questions and results for the second article by Cheung et al (2015) identified in the previous article (Yonkaitis & Maughan, 2018). You will note the results are not perfect.…”
Section: • • Systematic Reviews/meta-analysismentioning
confidence: 99%
“…As the only health professional in the building, school nurses must know how to access the most current evidence related to their practice. In previous articles in this series (Maughan & Yonkaitis, 2017;Yonkaitis & Maughan, 2018), we identified the three concepts of evidence-based practice (EBP) (student values, best evidence/data, and clinical expertise) that need to be considered when incorporating EBP into care of students ( Figure 1). These three concepts can be thought of as a process with six As: Ask, Acquire, Appraise, Apply, Assess, and Alert ( Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the evolving nature of COVID-19, much of the current evidence was not always published in the journals yet. The nurse authors also relied on other research studies, as well as experts such as the Centers of Disease Control and Prevention (CDC), the National Institute of Occupational Safety and Health, and the World Health Organization who compile various sources of evidence (Maughan & Yonkaitis, 2018; Yonkaitis, & Maughan, 2018b).…”
Section: Best Current Evidencementioning
confidence: 99%
“…This will help us recall what outcome(s) we were interested in achieving and determine what baseline data we need to collect. If we refer to the example we have been using throughout the series, our PICOT question was looking for an outcome that would decrease asthma exacerbations through the use of an evidence-based comprehensive care management program (Cheung et al, 2015;Maughan & Yonkaitis, 2018;Yonkaitis & Maughan, 2018b). When you Applied the evidence to your population, you followed the steps of program planning, and quality improvement, which are really the steps of the nursing process (ANA & NASN, 2017).…”
Section: Assessing Effectivenessmentioning
confidence: 99%